USOC-SCIENCE.ORG
Website of USOC-SCIENCE.ORG, the U.S. Olympic Committee's Sport Science and Technology site. The Sport Science and Technology Division provides assistance to USOC member organizations in three main areas. The first is service, the second is education, the third is development. Five principal areas of expertise are concentrated within the Division. These five areas are physical assessment, strength and conditioning, mental training, technique evaluation and technology.